2016
DOI: 10.1038/srep36501
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT evaluation of apical delta morphologies in human teeth

Abstract: The apical delta is an intricate system within the root canal and incompletely debridement may affect the long-term prognosis of root canal therapy. The aim of the present study is to investigate the morphologic features of apical deltas in human teeth with micro-computed tomography (micro-CT) using a centreline-fitting algorithm. One hundred and thirty-six apical deltas were detected in 1400 teeth. Molars had more apical deltas (15.8%) than anterior teeth (6.3%). In maxillary molars, the mesiobuccal root had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
2
24
1
1
Order By: Relevance
“…In a recent micro-CT study, Gao et al evaluated the incidence of apical deltas according to the different tooth types and reported that mandibular molar teeth commonly present these ramifications. 13 The results of the present study are in accordance with the report of Gao et al despite the different study populations. The present study only evaluated the mesial roots of mandibular molar since these roots are considered to have the most complex internal anatomies.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In a recent micro-CT study, Gao et al evaluated the incidence of apical deltas according to the different tooth types and reported that mandibular molar teeth commonly present these ramifications. 13 The results of the present study are in accordance with the report of Gao et al despite the different study populations. The present study only evaluated the mesial roots of mandibular molar since these roots are considered to have the most complex internal anatomies.…”
Section: Discussionsupporting
confidence: 93%
“…10 The increase in the prevalence rates might reflect the superiority of micro-CT techniques over the clearing method to detect fine anatomical variations. The mean number of apical delta ramifications per root was 4.45, which was similar to the results reported by Gao et al 13 The root canal configuration of most of the specimens presenting with apical deltas could not be classified according to the Vertucci classification (72.72%).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations